Small-signal oscillatory stability of a grid-connected PV power generation farm affected by the increasing number of inverters in daisy-chain connection - Zhou, Yi; Cao, Junzheng; Zhao, Jing (Frontiers in Energy Research, 2023)
Daisy-chain connection of inverters is one of the basic configurations of power collecting network in a grid-connected photovoltaic (PV) power generation farm. In this study, the total impact of a cluster of M similar inverters in daisy-chain connection in the PV farm is examined in the following two aspects: (1) Aggregated representation of the cluster of inverters is derived for stability study based on the dynamic equivalence. The derivation confirms the rationality to represent the cluster of inverters by an aggregated inverter connected to the external system via an equivalent reactance, which is the maximum eigenvalue of matrix of daisy-chain connection defined in the paper. (2) Analysis is conducted to indicate that the risk of oscillatory instability may be collectively induced by all the inverters in daisy-chain connection in the cluster. This explains why the increasing number of inverters may imply the possible instability risk of PV farm. An example power system with a grid-connected PV power generation farm is presented in the paper to demonstrate and evaluate the analytical conclusions obtained.